PERLAKUAN TERHADAP NARAPIDANA LANJUT USIA DENGAN DISABILITAS DI LEMBAGA PEMASYARAKATAN - Subroto, Mitro; Raihan, Muhammad (Ensiklopedia of Journal, 2024)
The treatment of elderly inmates with disabilities in correctional facilities presents significant challenges and ethical dilemmas. This research underscores the urgency of addressing the unique needs of this vulnerable population, as their rights and well-being are often overlooked. Employing a qualitative approach, the study involved interviews with inmates, staff, and experts to gather insights on their experiences and perspectives. The findings reveal systemic inadequacies in care and support, highlighting the need for tailored interventions and policies that promote dignity and rehabilitation. This research contributes to the discourse on prison reform and advocates for improved treatment standards for elderly inmates with disabilities.Keywords: elderly inmates; disabilities; correctional facilities; treatment; rehabilitation.